Virulence Traits and Population Genomics of the Black Yeast Aureobasidium melanogenum - Anja Černoša; Xiaohuan Sun; Cene Gostinčar; Chao Fang; Nina Gunde-Cimerman; Zewei Song (Journal of Fungi, 2021)
The black yeast-like fungus Aureobasidium melanogenum is an opportunistic human pathogen frequently found indoors. Its traits, potentially linked to pathogenesis, have never been systematically studied. Here, we examine 49 A. melanogenum strains for growth at 37 °C, siderophore production, hemolytic activity, and assimilation of hydrocarbons and human neurotransmitters and report within-species variability. All but one strain grew at 37 °C. All strains produced siderophores and showed some hemolytic activity. The largest differences between strains were observed in the assimilation of hydrocarbons and human neurotransmitters. We show for the first time that fungi from the order Dothideales can assimilate aromatic hydrocarbons. To explain the background, we sequenced the genomes of all 49 strains and identified genes putatively involved in siderophore production and hemolysis. Genomic analysis revealed a fairly structured population of A.melanogenum, raising the possibility that some phylogenetic lineages have higher virulence potential than others. Population genomics indicated that the species is strictly clonal, although more than half of the genomes were diploid. The existence of relatively heterozygous diploids in an otherwise clonal species is described for only the second time in fungi. The genomic and phenotypic data from this study should help to resolve the non-trivial taxonomy of the genus Aureobasidium and reduce the medical hazards of exploiting the biotechnological potential of other, non-pathogenic species of this genus.